2011
DOI: 10.1158/0008-5472.can-10-4351
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the MEK1(F129L) Activating Mutation as a Potential Mechanism of Acquired Resistance to MEK Inhibition in Human Cancers Carrying the B-RafV600E Mutation

Abstract: Although targeting the Ras/Raf/MEK pathway remains a promising anticancer strategy, mitogen-activated protein/extracellular signal-regulated kinase (ERK) kinase (MEK) inhibitors in clinical development are likely to be limited in their ability to produce durable clinical responses due to the emergence of acquired drug resistance. To identify potential mechanisms of such resistance, we established MEK inhibitor-resistant clones of human HT-29 colon cancer cells (HT-29R cells) that harbor the B-Raf V600E mutatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 37 publications
(46 reference statements)
2
55
0
1
Order By: Relevance
“…A similar MEK mutation, MEK1 F129L , displayed enhanced interaction with CRAF, thereby increasing intrinsic kinase activity of CRAF and, thus, circumventing MEK or BRAF inhibition. However, combination of RAF and MEK inhibitors overcome the observed drug resistance in this model system (37). Similarly, our data show that the combination of GSK2118436 and GSK1120212 effectively inhibits proliferation of cells with MEK1…”
Section: And Mek1supporting
confidence: 72%
“…A similar MEK mutation, MEK1 F129L , displayed enhanced interaction with CRAF, thereby increasing intrinsic kinase activity of CRAF and, thus, circumventing MEK or BRAF inhibition. However, combination of RAF and MEK inhibitors overcome the observed drug resistance in this model system (37). Similarly, our data show that the combination of GSK2118436 and GSK1120212 effectively inhibits proliferation of cells with MEK1…”
Section: And Mek1supporting
confidence: 72%
“…In addition, the identified mutations have all previously been shown to confer in vitro MEK inhibitor resistance in random mutagenesis experiments followed by stable transfection functional assays of MEK inhibitor resistance in BRAF mutant cells (11). The L115P and V211D mutations confer resistance by abrogating MEK inhibitor binding, while F129L also increases intrinsic kinase activity of MEK (10). All 3 of our cell lines retained the activating K-ras (G13D) allele.…”
Section: Molecular Mechanisms Of Mek Resistancementioning
confidence: 63%
“…Preclinical studies have identified multiple mechanisms of acquired resistance to BRAF inhibitors, including switching between RAF isoforms (4), upregulation of RTK or NRAS signaling (5), and reactivation of mitogen-activated protein kinase (MAPK) signaling via COT activation (6) or a MEK kinase activating mutation (7). Similarly, preclinical studies have identified distinct mechanisms by which cells acquire resistance to MEK inhibition, including amplification of mutant BRAF (8), STAT3 upregulation (9), or mutations in the allosteric pocket of MEK that can directly block binding of inhibitors to the MEK kinase or lead to constitutive MEK kinase activity (10,11). MEK mutations have also been described in tumor samples from patients treated with MEK (11) or BRAF inhibitors (7), showing clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…These include upregulation of receptor tyrosine kinase (RTK) signaling, amplification of BRAF, alternative splicing of mutant BRAF, emergence of mutations in RAS or MEK occurring concurrently with mutant BRAF, activation of EGFR-SFK-STAT3 signaling, and activation of NRAS signaling (10)(11)(12)(13)(14)(15)(16)(17)(18). MEK inhibitor resistance has been reported to arise as a result of mutations in the allosteric drugbinding pocket or amino-terminal negative inhibitory domain (19,20). Relative contribution of these varied mechanisms to disease progression in patients is presently unclear although most appear to lead to reactivation of ERK.…”
Section: Introductionmentioning
confidence: 99%